116k views
2 votes
Y = -2x + 1 4x + y = 9

User Kalithlev
by
4.7k points

1 Answer

5 votes

9514 1404 393

Answer:

(4, -7)

Explanation:

Maybe you want the solution to this system of equations.

About the easiest way to obtain it is to use a graphing calculator.

(x, y) = (4, -7)

_____

Additional comment

Since one of the equations gives an expression for y, it is a simple matter to substitute that for y in the other equation.

4x +(-2x +1) = 9

2x = 8 . . . . . . . . . . subtract 1 and simplify

x = 4

y = -2(4) +1 = -7 . . . use the first equation to find y

Y = -2x + 1 4x + y = 9-example-1
User Ben Swinburne
by
4.8k points